Combination Growth Factor Therapy via Electrostatically Assembled Wound Dressings Improves Diabetic Ulcer Healing In Vivo. Issue 14 (13th August 2015) - Almquist, Benjamin D.; Castleberry, Steven A.; Sun, Julia B.; Lu, Alice Y.; Hammond, Paula T.
Abstract : Chronic skin ulcerations are a common complication of diabetes mellitus, affecting up to one in four diabetic individuals. Despite the prevalence of these wounds, current pharmacologic options for treating them remain limited. Growth factor–based therapies have displayed a mixed ability to drive successful healing, which may be due to nonoptimal delivery strategies. Here, a method for coating commercially available nylon dressings using the layer‐by‐layer process is described to enable both sustained release and independent control over the release kinetics of vascular endothelial growth factor 165 and platelet‐derived growth factor BB. It is shown that the use of strategically spaced diffusion barriers formed spontaneously by disulfide bonds enables independent control over the release rates of incorporated growth factors, and that in vivo these dressings improve several aspects of wound healing in db/db mice. Abstract : Bioactive wound dressings created via layer‐by‐layer (LbL) self‐assembly enable independent control over the release kinetics of multiple growth factors to in vivo chronic wounds. Release kinetics are controlled by the spontaneous formation of 2D diffusion barriers within the LbL film. These dressings promote several aspects of wound healing in db/db mice including angiogenesis and the formation of granulation tissue.